On the role of land-surface hydrology schemes in simulating the daily maximum and minimum air temperatures of Australia using a regional climate model (RegCM4). Issue 3 (6th March 2023) - A. Anwar, Samy; Srivastava, Ankur; Zerouali, Bilel
Abstract: The present study addresses the possible effects of soil moisture changes on the simulated daily maximum and minimum air temperatures of Australia for a duration of 13 years. Therefore, the community land model version 4.5 (CLM4.5; coupled to the RegCM4) was used to represent the soil moisture and processes associated with it. The CLM4.5 has two land-surface hydrology schemes: TOPMODEL (TOP) and Variable Infiltration Capacity (VIC) and two simulations were conducted, namely: TOP and VIC. The results showed that VIC has lower soil moisture than TOP, leading to a decrease in vegetation transpiration, evaporation, and an increase in soil evaporation relative to TOP. However, there is no considerable difference between the two simulations compared with reanalysis products. In comparison to in-situ measurements, the RegCM4 can reasonably model the climatological annual cycle of mean air temperature (TMP) and its performance varies with the study site (e.g., RegCM4 overestimates TMP by 2.76 and 5.46 °C at Yanco and Tumbarumba, respectively). In summary, the simulated maximum and minimum air temperatures are sensitive to the physical parameterization of RegCM4 rather than variations in soil moisture. Likewise, improvements to the land-surface hydrology schemes TOP/VIC are required to better model Australia's daily maximum and minimum air temperatures. HIGHLIGHTS: RegCM4 succeeds in reproducing the spatial pattern of sensible and latent heat fluxes with respect to the ERA5. However, the difference between the two simulations themselves depends on the region as well as the austral season. Soil moisture changes do not impose a notable impact on the simulated surface energy balance, total cloud cover, and surface net radiation with respect to reanalysis products. Graphical Abstract